2014
DOI: 10.1021/jp5005133
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Structure of a Thermally Stable Hybrid Aluminosilicate Built with Only the Three-Ring Unit

Abstract: Organic–inorganic aluminosilicate hybrids are an attractive new class of materials that add organic functionalities to conventional properties of solid inorganic catalysts. ECS-17, a novel crystalline hybrid, was synthesized using 1,4-bis-(triethoxysilyl)-benzene as the sole silicon source. Its structure was solved by direct methods starting from high-resolution synchrotron X-ray diffraction data and is composed of inorganic layers, characterized by 10 rings, held together by phenylene rings. ECS-17 is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…40,41 Even layered ECS-type materials with inorganic sheets built from only three-ring secondary building units have been recently described. 42 However, to the best of our knowledge, these interesting materials have only been successfully prepared with rigid and non-catalytically active arylic fragments intercalated in the interlayer space.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Even layered ECS-type materials with inorganic sheets built from only three-ring secondary building units have been recently described. 42 However, to the best of our knowledge, these interesting materials have only been successfully prepared with rigid and non-catalytically active arylic fragments intercalated in the interlayer space.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the influence of boron on the synthesis performed using BTEB as bridged silsesquioxane was examined (Table 3). It should be emphasized the fact that, among the disilane precursors used so far, BTEB is the most versatile having led to the crystallization of different ECS phases (ECS-1, 40 ECS-2, 40 ECS-3, 40,41 ECS-17 42 ) by varying only slightly the composition of the reagent mixture. Among the numerous exploratory syntheses carried out with BTEB, NaAlO 2 and NaOH, one (entry BTEB-1) attracted our attention because it led to the formation of an unidentified product of low crystallinity but with interesting features (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…3b, facilitating the ab initio crystal structure determination and Rietveld refinement starting from synchrotron powder diffraction data. 42 Table 3 also reports the results of other synthesis runs performed for examining the influence of synthesis parameters on the characteristics of the crystalline product. The results indicated that pure and well crystallized ECS-14 can be obtained by keeping OH − /SiO 2 = 0.50 and H 2 O/SiO 2 = 20 or 40.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 2 more Smart Citations